1995
DOI: 10.1596/0-8213-3329-1
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Research on Land Degradation in Developing Countries

Abstract: This paper critically reviews the three main approaches to land degradation and conservation-the classic, populist and neo-liberal. The implications of these paradigm shifts are examined in terms of research needs. Next, the paper discusses the role of science and technology, and the origins and substance of differences in the perception, evaluation and diagnosis of degradation. Focus is then shifted to analyzing how farmers and pastoralists make decisions about resource use and management, and a research appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 96 publications
(64 reference statements)
0
50
0
Order By: Relevance
“…The Economic or Neo-liberal approach focuses on the policy environment. Proponents of this approach contend that it is necessary to comprehend the structures of incentives that discourage land users from adopting sustainable technologies (Biot et al, 1995). They assert that 'pull' and 'push' factors are important in explaining land degradation in SSA.…”
mentioning
confidence: 99%
“…The Economic or Neo-liberal approach focuses on the policy environment. Proponents of this approach contend that it is necessary to comprehend the structures of incentives that discourage land users from adopting sustainable technologies (Biot et al, 1995). They assert that 'pull' and 'push' factors are important in explaining land degradation in SSA.…”
mentioning
confidence: 99%
“…Only 18% of the respondents have adopted fish farming as major occupation, the rest 82% were engaged in agriculture, other business and government jobs. Biot et al (1995) suggested that 'different behaviour is as much a function of different opportunities and constraints as of different perception'. Even within the farm households, the ability to make decision on resource use and technology adoption varies according to age, gender and other category and actual decision can depend on a complex bargaining process amongst the members (Ellis, 1993;Jackson, 1995;Biot et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[6] grouped these approaches into three major types: top-down interventions, populist or farmer-first, and neoliberal approaches. Building from the farmerfirst and sustainable livelihood principles but extending and incorporating important elements from various theories and practical realities, [7] have developed a broader conceptual framework for the analysis of factors conditioning the adoption and adaptation of smallholder natural resource management technologies in general.…”
Section: Conceptual Framework Of the Studymentioning
confidence: 99%